Control of the Adaptive Immune Response by Tumor Vasculature - Mauge, Laetitia; Terme, Magali; Tartour, Eric; Helley, Dominique (Frontiers in Oncology, 2014)
The endothelium is nowadays described as an entire organ that regulates various processes: vascular tone, coagulation, inflammation, and immune cell trafficking, depending on the vascular site and its specific microenvironment as well as on endothelial cell-intrinsic mechanisms like epigenetic changes. In this review, we will focus on the control of the adaptive immune response by the tumor vasculature. In physiological conditions, the endothelium acts as a barrier regulating cell trafficking by specific expression of adhesion molecules enabling adhesion of immune cells on the vessel, and subsequent extravasation. This process is also dependent on chemokine and integrin expression, and on the type of junctions defining the permeability of the endothelium. Endothelial cells can also regulate immune cell activation. In fact, the endothelial layer can constitute immunological synapses due to its close interactions with immune cells, and the delivery of co-stimulatory or co-inhibitory signals. In tumor conditions, the vasculature is characterized by abnormal vessel structure and permeability, and by specific phenotype of endothelial cells. All these abnormalities lead to a modulation of intratumoral immune responses and contribute to the development of intratumoral immunosuppression, which is a major mechanism for promoting the development, progression and treatment resistance of tumors. The in-depth analysis of these various abnormalities will help defining novel targets for the development of antitumoral treatments. Furthermore, eventual changes of the endothelial cell phenotype identified by plasma biomarkers could secondarily be selected to monitor treatment efficacy.